Penerapan Strategi Think, Talk, Write Dalam Kosa Kata Bahasa Inggris Dengan Menggunakan Film - Ibrahim Guntur Nuary (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
English language indeed is international language, but in Indonesiaitself to mastering English language it’s hard to do, because of the lackof vocabulary. Vocabulary is the important part to mastering Englishlanguage. To gain the vocabulary, there are many ways, one of them iswatching movie. This research aimed to find out the learners in XI IPA1 and XI IPA 2 grades how they gain the vocabulary through subtitledmovie by using think, talk, write strategy. The data will be searched byqualitative descriptive. The data will be taken from the movie andteacher perspective about the strategy that teacher did. The result ofthis study to know how much the learners between male and femalegain the vocabulary through subtitled movie by using think, talk, writestrategy. The learners female and male taken two class and betweenlearners male and female the class is not separated. The movie entitled“Frozen”. From the movie, the learners should be written thevocabulary what they got from the movie. The class is devided into fivegroups, then all of groups should provide the words they got from themovie and then mention the words to other groups in order to thegroups know the words from other groups and its strategy was reallyworks to make students got the words a lot from the movie. The result ofthis study is the learners got a lot of vocabularies between XI IPA 1 andXI IPA 2 grades through TTW strategy by using movie and the teachergave the feedback of vocabulary from the movie. Such as the words ofworth, accident, gates staff,and party from the movie.